Imidazole-Fused Enediynes by Selective C5–C4 Alkynylations of 4,5-Dibromoimidazoles - Lessi, Marco; Panattoni, Alessandro; Guglielmero, Luca; Minei, Pierpaolo; Bellina, Fabio (Synthesis, 2019)
An efficient synthesis of symmetrical 1,2-disubstituted 4,5-dialkynylimidazoles by Sonogashira alkynylation of the corresponding 4,5-dibromo derivatives was developed. Moreover, through a careful tuning of the palladium ligand, unsymmetrical 1,2-disusbtituted 4,5-dialkynylimidazoles were also prepared through a regioselective C5 alkynylation of 4,5-dibromoimidazoles, followed by a second alkynylation involving the 4-bromo derivatives so obtained. This interesting class of imidazole-fused enediynes is also able to give thermal Bergman cycloaromatization (BC), as proved by DSC experiments.
Keywords: imidazoles; Sonogashira reaction; regioselectivity; enediynes; Bergman cyclization; palladium; copper; cross-coupling